The Relationship between Management Practices and Safety - Siew, Lee Cheng; Florianna Lendai, Michael Mulok; Hana, Hamidi; Siti Mariam, Abdullah (Faculty of Cognitive Sciences and Human Development, Universiti Malaysia Sarawak (UNIMAS), 2018)
Work-related accidents is a controversial topic in Malaysia as evidenced by the increased number of occupational accidents throughout the years. The purpose of this research is to examine the relationship between management practices and safety performance in an or-ganization. The four management practices investigated are (a) training, (b) management commitment, (c) communication and feedback, and (d) employee involvement. The most effective safety practice is also identified. The data was collected at a manufacturing com-pany located in Shah Alam, Malaysia using closed-ended questionnaire. 95 respondents from the production line were involved in this study. The result found that training had a very weak relationship to the safety performance while the management commitment, as well as the communication and feedback, revealed to have a weak impact on safety perfor-mance. On the other hand, the analysis showed that employee involvement is the most ef-fective safety practice to the safety performance, as it had a moderate impact on safety per-formance.